Implementasi Telemedicine Sebagai Upaya Peningkatan Akses Dan Kualitas Pelayanan Kesehatan Masyarakat Dipedesaan - Fandani, Mona; Kosasih, Kosasih (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2025)
The rapid advancement of digital technology has encouraged the implementation of telemedicine as an alternative solution to improve health services, especially in rural areas with limited access to health facilities. This study aims to explore the implementation of telemedicine as an effort to improve access and quality of health services at Julok Community Health Center, Aceh Utara. The research employed a qualitative descriptive-exploratory method, with data collected through in-depth interviews, observations. Data were analyzed thematically to identify patterns and meanings related to the implementation of telemedicine. The findings indicate that telemedicine provides easier access for patients to obtain medical consultations, reduces geographical and financial barriers, and increases efficiency in health service delivary. In terms of service quality, telemedicine was found to facilitate faster renponse times and better continuity of care. However, limitations were identified, including unstable internet connectivity and difficulties in establishing accurate diagnoses without face-to-face examination. Based on these findings, it can be concluded that telemedicine plays an important role in supporting health sevice delivery in rural areas, but it cannot fully replace conventional services. It is recommended that further studies examine the clinical effectiveness of telemedicine and its long-term impact on patient health outcomes. Practically, strengthening digital infrastructure and digital literacy training is necessary to optimize the use of telemedicine in primary health care.